Morphological evaluation using MRI of the olfactory filaments (fila) in a post-traumatic olfactory rat model - Zhi-Fu Sun (KeAi Communications Co., Ltd., 2018)
Objective: To investigate whether magnetic resonance imaging (MRI) can be used to directly assess olfactory bulb (OB) lesions and quantify the associated morphological changes of olfactory filaments (OF), also known as fila, in an in vivo OB-lesion rat model of the brain. Methods: A surgical group (n = 5) of male Sprague–Dawley rats was subjected to the unilateral damage of the OB by a steel needle. The control group (n = 5) did not receive surgery. To assess olfactory system injury in vivo, T2-weighted MRI images were acquired in an oblique plane at a 30° angle from transverse plane one day after surgery. These brain regions were also assessed in the controls. The olfactory function was evaluated using the buried food pellet test (BFPT) 5 days before and after surgery. Results: The OF could be clearly observed on the MRI images from all animals. The left and right OF mean lengths (mm) were similar in the control group (0.81 ± 0.18 vs 0.89 ± 0.17, P > 0.05). In the surgical group, the OB was partially injured in all rats. These rats did not show differences in OF length between left- and right-side (0.83 ± 0.18 vs 0.93 ± 0.24, P > 0.05) at the time of measurement. The time (sec) required to find the food pellets in the BFPT was longer after than before the surgery (83.80 ± 34.37 vs 231.44 ± 53.23, P < 0.05). Conclusions: MicroMRI may be a feasible tool to evaluate the OF and OBs in rat models. The unilateral partial OB lesion model appears to be an effective post-traumatic olfactory dysfunction model. Keywords: MicroMRI, Olfactory fila, Olfactory bulb, Post-traumatic olfactory dysfunction model, Rat